Mobile applications for use in Teaching Chemistry: a brief review (Research, Society and Development, 2019)
The use of mobile applications for smartphones can become an ally of the teacher in the Teaching of Chemistry. Like this, this work aims to present some mobile applications for Smartphones, compatible with the Android operating system, which have potential for use in teaching chemistry, as well as present a brief analysis on them. the applications were searched on the Google Play Store platform, and a total of 5 were found, all free. A class was held in the Chair of Methodology of Teaching of Chemistry in the course of Chemistry Degree of the IFCE - Maracanaú Campus so that the teachers in initial formation could evaluate the potentialities of the selected applications. After the analysis, it was found that they have the potential to be used by the teacher in the chemistry classes.